2021
DOI: 10.3390/healthcare9040377
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cervical Spine Mobilization on Respiratory Function and Cervical Angles of Stroke Patients: A Pilot Study

Abstract: The forward head posture (FHP) of stroke patients has a negative impact on respiratory function. Cervical spine mobilization is a manual therapy technique that used to prevent and treat FHP and respiratory function. This pilot study investigated whether cervical spine mobilization can effectively improve outcomes following FHP and respiratory function of stroke patients. Twenty-four patients participated in our assessor-blinded randomized controlled trial. All the participants received neurodevelopmental treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
4
0
1
Order By: Relevance
“…In our study, we achieved greater improvement in FHP scores in the SG using CM. A limited number of past studies have shown that CM may improve FHP, cervical position sense, swallowing function, and respiratory function in SI (An et al, 2021; An & Park, 2021; Jeon et al, 2020). These results are consistent with ours.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we achieved greater improvement in FHP scores in the SG using CM. A limited number of past studies have shown that CM may improve FHP, cervical position sense, swallowing function, and respiratory function in SI (An et al, 2021; An & Park, 2021; Jeon et al, 2020). These results are consistent with ours.…”
Section: Discussionmentioning
confidence: 99%
“…Spinal mobilization techniques used in manual spinal treatment activate the descending pathway from the peritubular gray region (PAG) of the midbrain, reduce superficial neck flexion, and increase deep flexor activity. It has a neurophysiological effect on the strength of the neck muscles 21 .…”
Section: Sling-based Manual Therapy and Stabilization Exercisementioning
confidence: 99%
“…This intervention approach stepped forward tissue elasticity and range of motion around the neck, alleviated it, relaxation, impaired muscle function, and reduced soft tissue swelling and inflammation 16 . Pain alleviation may additionaly reduce motor system depression and partially enhance function 21 . Some research confimed that a combination of manual therapy and stabilizing exercise become extra powerful in treating FHP than stabilizing exercise alone 14,23,19 .…”
Section: Combination Sling-based Manual Therapy and Stabilization Exe...mentioning
confidence: 99%
“…To assist the paralysis of the principal respiratory muscle and compensate for the decreased respiratory function of stroke patients, overuse of the respiratory accessory muscles, such as the sternocleidomastoid and scalenus muscles, may occur and may move the head forward [9]. This postural change affects the anteroposterior diameter of the chest cage as well as the volume of the lungs, thereby affecting the respiratory system [10].…”
Section: Introductionmentioning
confidence: 99%